TALPID3 and ANKRD26 selectively orchestrate FBF1 localization and cilia gating - Hao Yan (Nature Communications, 2020)
Most cells possess sensory cilia, which need to be gated properly. Here the authors show that the C. elegans proteins TALP-3 and ANKR-26 coordinate cilia gating in the context of transition fibers and that this mechanism is conserved in mammalian cells and likely implicated in certain ciliopathies.